New biological activity of the polysaccharide fraction from Cantharellus cibarius and its structural characterization. (1st December 2018) - Nowacka-Jechalke, Natalia; Nowak, Renata; Juda, Marek; Malm, Anna; Lemieszek, Marta; Rzeski, Wojciech; Kaczyński, Zbigniew
Highlights: Polysaccharides from C. cibarius inhibit COX-1 and COX-2 activity. Polysaccharides from C. cibarius stimulate the growth of Lactobacillus strains. Polysaccharides from C. cibarius inhibit a proliferation of colon cancer cells. The major polysaccharide of the investigated fraction was →6)-α-D-Manp-(1→. C. cibarius constitutes a dietary available chemopreventive agent. Abstract: One of the most commonly consumed mushrooms in Europe is Cantharellus cibarius, also known as chanterelles. Therefore, the investigation of the pro-health properties of crude polysaccharides from this species was performed. The obtained results indicate that the polysaccharide fraction from C. cibarius inhibits the activity of both COX-1 and COX-2. Moreover, the prebiotic potential was revealed in relation to Lactobacillus strains. Crude polysaccharides were found to inhibit the proliferation of colon cancer cells with the simultaneous absence of toxicity towards normal cells. The purification and structural characterization of the examined polysaccharide fraction from C. cibarius indicates that it consists of one monosaccharide in the repeating unit →6)-α-D-Manp-(1→. The presented activities indicate for the first time that this edible mushroom possesses interesting chemopreventive potential, especially against colon cancer.